How Will International Students Spend Their Vacation? - Yan, Ruifeng; Christensen, Ami; Li, Yifan; Du, Xinyan; Jiao, Tianqi (My University, 2019)
Nowadays, international students are under great pressures, so they are looking forward to the vacation to relax. However, it is also important for them to spend vacation wisely. In order to help them make full use of their vacation and improve the qualities of their vacation, our project investigate how international students spend their time on vacation.
Color poster with text, chart, and images.
Keywords: Posters; Department of Languages; International students--Wisconsin--Eau Claire; Travel--United States; Leisure-Social aspects